Three new species of Canthonella Chapin from Hispaniola, with new records and Nomenclatural changes for West Indian dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) - Ivie, Michael A.; Philips, T. Keith (Zootaxa, 2008)
Three new species, Canthonella jarmilae, Canthonella quesquaya, and Canthonella sikesi NEW SPECIES, are described from Hispaniola. New distribution records for Canthochilum taino Matthews and Canthonella parva Chapin expand the known range of these Puerto Rican Bank species to the northern Virgin Islands. Colonization by the Old World species Digitonthophagus gazella (Fabricius) on Jamaica, Hispaniola, Puerto Rico, St. Croix, St. Kitts, Montserrat and Guadeloupe is documented for the first time, and the mainland American species Pseudocanthon perplexus (LeConte) is recorded from Grand Bahama Island, a first record for the West Indies. Onthophagus albicornis Palisot de Beauvois and Onthophagus capitatus Laporte are re-elevated to full species NEW STATUS, and their allopatric distribution on Hispaniola documented. A list of the 45 known species from the Greater Antilles and Bahama Islands is included.